2024
DOI: 10.1021/acs.jafc.3c07260
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus brevis-Fermented Gamma-Aminobutyric Acid Ameliorates Depression- and Anxiety-Like Behaviors by Activating the Brain-Derived Neurotrophic Factor-Tropomyosin Receptor Kinase B Signaling Pathway in BALB/C Mice

Hyeongyeong Kim,
Hoon Kim,
Hyung Joo Suh
et al.

Abstract: This study investigated the effects of Lactobacillus brevis-fermented gamma-aminobutyric acid (LB-GABA) on depressive and anxiety-like behaviors with the underlying molecular mechanism in a chronic stress model of BALB/c mice. LB-GABA attenuates both neuronal cell death and the increase of monoamine oxidase activity induced by hydrogen peroxide. Behavioral tests revealed that GABA significantly increased sucrose preference and reduced immobility time in both tail suspension and forced swimming tests. LB-GABA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Dietary interventions with probiotics may increase diversity of intestinal microbiome and improve mental health outcomes. Probiotics can modulate neurotransmitters and proteins (GABA, glutamate, histamine, serotonin, and BDNF) by gut-brain axis, and are essential to control the neural excitatory-inhibitory balance, mood, and anxiety ( 37 , 38 ). Bravo et al ( 16 ) identified that ingestion of the lactic acid bacteria Lactobacillus rhamnosus resulted in vagus nerve dependent anxiolytic behavioral effects and change of GABA receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary interventions with probiotics may increase diversity of intestinal microbiome and improve mental health outcomes. Probiotics can modulate neurotransmitters and proteins (GABA, glutamate, histamine, serotonin, and BDNF) by gut-brain axis, and are essential to control the neural excitatory-inhibitory balance, mood, and anxiety ( 37 , 38 ). Bravo et al ( 16 ) identified that ingestion of the lactic acid bacteria Lactobacillus rhamnosus resulted in vagus nerve dependent anxiolytic behavioral effects and change of GABA receptor expression.…”
Section: Discussionmentioning
confidence: 99%